ANALISIS HUBUNGAN SIMULTANITAS ANTARA KEBIJAKAN HUTANG DAN KEBIJAKAN DIVIDEN - Ananda Dian Damayanthi; Puji Harto (Diponegoro Journal of Accounting, 2016)
The purpose of this research is to analyze the simultaneous relationship between debt policy and dividend policy, the influence of market to book value, concentration ownership, return on assets, and firm size to dividen policy and the influence of market to book value, concentration ownership, liquidity, and firm size to debt policy of non-financial and non-banking companies were listed on Indonesia Stock Exchange.Sample in this research were selected by using purposive sampling method with some selected criterias. 72 companies listed on 2010 until 2014’s Indonesia Stock Exchange were chosen as sample. The statistic method that used in this research are descriptive analysis, classical assumption test (Normality test, Heteroscedasticity test, multicollinearity test, autocorrelarity test), simultaneous equation models analysis (Two Stage Least Squares), Hausman Test, hypothesis test (F-statistics Test, t-statistics test, and Coefficient of Determination Test).The results showed that debt policy is related positive significant to dividend but dividend policy is related positive not significant simultaneously to order debt policy. Liquidity has a negative significant to debt; concentration ownership has a negative and not significant to debt policy; firm size and investment opportunity set have a positive and not significant effect debt policy. Concentration ownership and profitability have a significant positive effect to dividend policy; firm size and investment opportunity set have a positive not significant effect dividend policy.